The influence of flavours and halal labels on purchasing decisions - Yunas, Muhammad Faisal Yunas; Yusuf, Muhammad Ali; Sekarini, Ratih Ayu (Junal Ilmu Manajemen, 2025)
Indonesian cuisine is as diverse as its multicultural ethnicities and regions. Indonesian cuisine is characterised by a variety of spices, cooking methods and local ingredients. Some of these have influences from India, China, the Middle East and Europe (Indonesian Embassy). The diversity of traditional food is also influenced by the variety of local ingredients available in each region. Every consumer has a particular flavour culinary preference. From street vendors to fine dining restaurants and cafes, you will find a variety of menus with unique flavours, both traditional and present day. The research location was held in Bojong Kulur Village, Gunung Putri District, Bogor with a total of 32 respondents of SME culinary business owners. This research uses quantitative methods. With information collection techniques in the form of observation, document study, questionnaire collection, and interviews. The information analysis techniques used are: linear regression, correlation, and heterocdestige methods using SPSS application collected from surveys, interviews and case studies.